2020
DOI: 10.3389/fimmu.2020.00275
|View full text |Cite
|
Sign up to set email alerts
|

Unleashing Natural Killer Cells in the Tumor Microenvironment–The Next Generation of Immunotherapy?

Abstract: The emergence of immunotherapy for cancer treatment bears considerable clinical promise. Nevertheless, many patients remain unresponsive, acquire resistance, or suffer dose-limiting toxicities. Immune-editing of tumors assists their escape from the immune system, and the tumor microenvironment (TME) induces immune suppression through multiple mechanisms. Immunotherapy aims to bolster the activity of immune cells against cancer by targeting these suppressive immunomodulatory processes. Natural Killer (NK) cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
95
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(96 citation statements)
references
References 337 publications
(347 reference statements)
1
95
0
Order By: Relevance
“…The clinical response of dog#3, categorized as WHO stage I, was SD. It is well known that the efficacy of cytotoxic antibodies depends on the number of tumor-infiltrating effector cells (e.g., NK cells, macrophages), and cytotoxic antibodies show stronger anti-tumor effects against tumors with a larger number of infiltrating effector cells [ 67 , 68 ]. In canine malignant melanoma, the number of infiltrating effector cells is inversely correlated with tumor stage [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…The clinical response of dog#3, categorized as WHO stage I, was SD. It is well known that the efficacy of cytotoxic antibodies depends on the number of tumor-infiltrating effector cells (e.g., NK cells, macrophages), and cytotoxic antibodies show stronger anti-tumor effects against tumors with a larger number of infiltrating effector cells [ 67 , 68 ]. In canine malignant melanoma, the number of infiltrating effector cells is inversely correlated with tumor stage [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical trials have tested different NK cell-based therapies for cancer, particularly for hematological malignancies, but their efficacy was not as high as anticipated [227]. Therefore, increasing the activity of NK cells against cancer is a promising avenue for the clinical application of immunotherapy [228]. Recently, two groups showed that GSK3β inhibition in normal peripheral NK cells enhances their cytotoxic effects against acute myeloid leukemia (AML) cells [143,144].…”
Section: Gsk3β and Cancer Immunotherapymentioning
confidence: 99%
“…Although blockade of LAG-3 alone seemed to have no effect on NK cell lysis against various targets, several reports showed that chronic stimulation of NK cells could increase LAG-3 surface expression and that of other co-inhibitory receptors, which contributed to NK cell exhaustion and weakened the anti-tumor activity of NK cells. In this situation, blocking LAG-3 could restore NK cells' cytotoxic capacity ( 93 , 94 ). In a 4T1 mouse lung metastatic breast cancer model, lung infiltrating NK cells manifested a dysfunctional state, with impaired lytic activity and low capacity to produce IFN-γ, concomitant with increased expression of inhibitory receptors and the loss of activating receptors.…”
Section: The Key Nk Cell Checkpoint Receptors or Molecules That Contrmentioning
confidence: 99%